Pengaruh Budaya Organisasi, Manajemen Sumber Daya Manusia, Motivasi Dan Kepuasan Kerja Terhadap Kinerja Kerja Dit Intelkam Polda Metro Jaya - Heriyanto; Muhamad Arief Noor; Joned Ceilendra Saksana (Ekopedia: Jurnal Ilmiah Ekonomi, 2025)
The competence of Indonesian National Police officers is a necessity that cannot be postponed any longer. Bold steps are needed to quickly, precisely, and gradually improve the quality of competency-based human resource development, incorporating components of knowledge, skills, and attitude. Developing and empowering human resources requires an organizational culture and work motivation to improve overall service to the community. The purpose of this study was to determine the influence of Organizational Culture, Human Resource Management, Work Motivation, and Job Satisfaction on the performance of the Traffic Directorate of the Jakarta Metropolitan Police. The population and sample were all Traffic Directorates of the Jakarta Metropolitan Police. The results of the study indicate that the variables of Organizational Culture, Human Resource Management, motivation and Job Satisfaction with an Fcount value of 219.295 with an Ftable of 3.35, because the tcount value of 219.295> ttable value of 3.35 and the significance value of 0.000 <0.05, it can be concluded that Ho is rejected, meaning that Organizational Culture, Human Resource Management and motivation together have a significant effect on the performance of members of the Traffic Directorate of the Metro Jaya Regional Police. Meanwhile, from the determination coefficient test, it is known that the R value is 0.950, which means that there is a very strong relationship between the variables of Organizational Culture, Human Resource Management, and motivation with the performance of members of the Traffic Directorate of the Metro Jaya Regional Police. Meanwhile, the R-Square value is 0.902 so that the independent variables consisting of Organizational Culture, Human Resource Management, motivation and Job Satisfaction contribute an influence of 0.902 or 90.2% to the performance of members of the Traffic Directorate of the Metro Jaya Regional Police while the rest is influenced by other factors not included in the model.